Portal de Biodiversidade de Chalcidoidea, um recurso online para informações e identificação taxonômica - Dal Molin, Ana; Tavares, Marcelo T.; Monjardim, Gustavo E. (Entomological Communications, 2019)
The scarcity of easily accessible high-quality, up-to-date information about certain taxa and difficulties using dichotomous taxonomic keys have long been issues raised by the scientific community. This problem is especially evident regarding resources in Portuguese. This article introduces the Chalcidoidea Biodiversity Portal (Portal de Biodiversidade de Chalcidoidea), a web resource which aims to provide researchers, educators and other members of the community with tools to aid in the taxonomic identification of chalcid wasps, as well as a continuously updated texts with recent advancements in the area. The main differential of the portal is a section including freely accessible multiple-entry keys. The interface for multiple-entry keys are desktop- and mobile-friendly, allowing the user to select illustrated features by clicking, progressively eliminating alternative results until only one is left. The researcher interface allows them to easily update information and to upload developed keys using the Structured Descriptive Data (SDD 1.1) format. Our main objective is to foster communication for research groups focusing on Chalcidoidea in the Neotropical region, including sectors focused on biological control. The web site is hosted at http://chalcidoidea.ufes.br.